Laue functions model vs Scherrer equation in determination of graphene layers number on the ground of XRD data - Beti Andonovic, Misela Temkov, Abdulakim Ademi, Aleksandar Petrovski, Anita Grozdanov, Perica Paunović, Aleksandar Dimitrov (University of Chemical Technology and Metallurgy, Sofia, Bulgaria, 2014)
The present study reports data referring to the determination of the layers of graphene samples obtained by electrolysis in aqueous electrolytes and molten salts using a reverse change of the potential applied. The analysis, based on the calculation of 002 XRD peak intensities, is carried out with the application of the Scherrer equation and the Laue functions model. The latter results differ from those obtained on the ground of Scherrer equation but coincide with data obtained by Raman spectroscopy and other methods. This is attributed to the multi-layer structure of the graphene samples studied.